The Value of Glioma Extent of Resection in the Modern Neurosurgical Era - Hardesty, Douglas A.; Sanai, Nader (Frontiers in Neurology, 2012)
Objective: There remains no general consensus in the neurosurgical oncology literature regarding the role of extent of glioma resection in improving patient outcome. Although the value of resection in establishing a diagnosis and alleviating mass effect is clear, there is less certainty in ascertaining the influence of extent of resection. Here, we review the recent literature to synthesize a comprehensive review of the value of extent of resection for gliomas in the modern neurosurgical era. Methods: We reviewed every major peer-reviewed clinical publication since 1990 on the role of extent of resection in glioma outcome. Results: Thirty-two high-grade glioma articles and 11 low-grade glioma articles were examined in terms of quality of evidence, expected extent of resection, and survival benefit. Conclusions: Despite limitations in the quality of data, mounting evidence suggests that more extensive surgical resection is associated with longer life expectancy for both low- and high-grade newly-diagnosed gliomas.